2022
DOI: 10.3390/cells11172758
|View full text |Cite
|
Sign up to set email alerts
|

Lung Organoids as Model to Study SARS-CoV-2 Infection

Abstract: Coronavirus disease-2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has become a global pandemic and has severely affected socio-economic conditions and people’s life. The lung is the major target organ infected and (seriously) damaged by SARS-CoV-2, so a comprehensive understanding of the virus and the mechanism of infection are the first choices to overcome COVID-19. Recent studies have demonstrated the enormous value of human organoids as platforms for virological re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…Together with organoid modeling and SARS-CoV-2 entry factor expression analysis, this study revealed a proximal-distal infection gradient along the upper and lower respiratory tract (133). Additionally, multiple studies showed that SARS-CoV-2-infected cells in alveolar organoids exhibit gene expression programs similar to those seen in COVID-19 autopsy samples (43,(134)(135)(136). This includes elevated levels of various proinflammatory chemokines (CXCL10, CXCL11, and CXCL17), interferon pathway components (type I and III IFNs), cell death pathway components (TNFSF10, CASP1, CASP4, CASP5, and CASP7), and downregulation of surfactant-related genes (SFTPC, SFTPD) (43,128,130).…”
Section: Applications Of Organoid Models To Study Infectious Biologymentioning
confidence: 55%
“…Together with organoid modeling and SARS-CoV-2 entry factor expression analysis, this study revealed a proximal-distal infection gradient along the upper and lower respiratory tract (133). Additionally, multiple studies showed that SARS-CoV-2-infected cells in alveolar organoids exhibit gene expression programs similar to those seen in COVID-19 autopsy samples (43,(134)(135)(136). This includes elevated levels of various proinflammatory chemokines (CXCL10, CXCL11, and CXCL17), interferon pathway components (type I and III IFNs), cell death pathway components (TNFSF10, CASP1, CASP4, CASP5, and CASP7), and downregulation of surfactant-related genes (SFTPC, SFTPD) (43,128,130).…”
Section: Applications Of Organoid Models To Study Infectious Biologymentioning
confidence: 55%
“…Given traditional cell lines cannot recapitulate the physiologically relevant kinetics of in vivo SARS‐CoV‐2 infection, human organoids provide promising models for drug discovery of COVID‐19. The respiratory system is the initial viral target, thus human lung organoids were used to test the efficacy of drugs and compounds, focusing on viral entry and replication 135,136 . For instance, Xu et al demonstrated that inhibition of receptor‐interacting serine/threonine‐protein kinase 1 (RIPK1 kinase) caused by RIPK1 inhibitor Nec‐1s reduced viral load and inflammatory responses in infected lung organoids 137 .…”
Section: Human Organoids For Drug Discovery Of Sars‐cov‐2mentioning
confidence: 99%
“…The respiratory system is the initial viral target, thus human lung organoids were used to test the efficacy of drugs and compounds, focusing on viral entry and replication. 135 , 136 For instance, Xu et al demonstrated that inhibition of receptor‐interacting serine/threonine‐protein kinase 1 (RIPK1 kinase) caused by RIPK1 inhibitor Nec‐1s reduced viral load and inflammatory responses in infected lung organoids. 137 The results suggest that the function of RIPK1 in SARS‐CoV‐2 propagation and suppression of RIPK1 might provide a strategy for COVID‐19 therapeutics and prevention.…”
Section: Human Organoids For Drug Discovery Of Sars‐cov ...mentioning
confidence: 99%
“…SARS-CoV-2 infection toward various cell types has been performed, which includes studies using pulmonary cancer cells Calu-3, kidney cells 293FT, liver cells Huh7, colon cancer cells CaCO2, and Vero (Hoffmann et al, 2020; Katopodis et al, 2022; Saccon et al, 2021). In addition, organ tropisms have been studied using post-mortem tissue samples from COVID-19 patients and organoid models (Peng et al, 2022). Based on these studies, SARS-CoV-2 tropisms are strongly related to hACE2 expression as its target receptor and TMPRSS2 protease, which enhances the viral entry process.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,5 ) In addition, organ tropisms have been studied using post-mortem tissue samples from COVID-19 patients and organoid models. 6 ) Based on these studies, SARS-CoV-2 tropisms are strongly related to hACE2 expression as its target receptor and TMPRSS2 protease, which enhances the viral entry process. SARS-CoV-2 infection involves the interaction of spike glycoprotein with hACE2, with or without spike priming by TMPRSS2, to facilitate cell entry through endocytosis or membrane fusion mechanisms.…”
Section: Introductionmentioning
confidence: 99%